The Impact of AR-based Product Visualization on Customer Satisfaction in the Wall Paint Industry - Athoillah, Fikri Aziz (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
This study aims to analyze the impact of Augmented Reality (AR)-based Product Visualization on Customer Satisfaction in the wall paint industry. A quantitative survey method was employed, collecting primary data through questionnaires from customers of wall paint companies. Regression analysis was used to analyze the data and identify the influence of the independent variable (AR-based Product Visualization) on the dependent variable (Customer Satisfaction). The research results reveal that AR-based Product Visualization significantly affects customer satisfaction (t calculated > t critical, 11.155 > 1.980). Approximately 52.6% of the variation in customer satisfaction can be explained by AR-based Product Visualization. These findings indicate that the implementation of AR technology in the wall paint industry can enhance customer satisfaction.